What is new in Obstetric Anesthesia in 2020: a focus on research priorities for maternal morbidity, mortality, and postpartum health. (August 2022) - Lim, G.
Highlights: 2020 USA maternal morbidity and mortality uncovered areas for systematic improvement. Anesthesiology research should focus on health disparities, mental health and pain management. Policy and health systems are also important areas for researchers. Abstract: Advances in obstetric anesthesiology have historically exemplified how scientific progress can have a transformational impact on patient safety practices. Profound reductions in anesthesia-related maternal mortality in the 20th century highlighted the specialty of anesthesiology as a leader in safety and care quality. In 2020, maternal health faces new crises: preventable maternal mortality trends worldwide continue to stagnate, and in the United States of America, mortality rates are increasing, attributable to structural care limitations, systemic racism, and social determinants of health. Postpartum health offers improvement opportunities given high rates of maternal deaths occurring within the first postpartum year, particularly in the areas of mental health, cognition, and recovery. Obstetric anesthesiologists have unique perspectives on systems of care, education and training, and device innovation. An interdisciplinary team approach to research and innovation, as well as systems based and health policy work, presents an opportunity for anesthesiologists to contribute to solutions that reduce maternal morbidity and mortality and improve postpartum health for all people.